2015
DOI: 10.4012/dmj.2015-057
|View full text |Cite
|
Sign up to set email alerts
|

The effect of multi-ion releasing filler contents on the dentin bond strength of an adhesive resin developed for direct pulp-capping

Abstract: We aimed to evaluate the microtensile bond strength (µTBS) of experimentally developed all-in-one adhesives containing surface reaction-type pre-reacted glass-ionomer (S-PRG) filler as a direct pulp-capping agent. Flattened dentin surfaces of extracted human molars were treated with four experimental adhesives of different S-PRG filler content (group 1: 0 wt%, group 2: 13 wt%, group 3: 27 wt% and group 4: 40 wt%) and Fluorobond Shakeone as the control. The beam samples were made and attached to the testing dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…These results suggested that B has an effect to increase the activity of ALP not only on bone marrow-derived cells but also on dental pulp-derived hDPSCs in the S-PRG filler-derived multi-ion system. Thus, the results above suggest the possibility that S-PRG fillers that slowly release B may contribute to promoting calcification in biological tissues, as well as the possibility that S-PRG fillers may promote mineralisation in dentin adjacent to the dental pulp, such as pulp-capping materials [33][34][35] . In addition, the comparison between E3 and the control medium showed the cell proliferation effect and ALP activity decreased in E3 compared with the control, despite that the concentration of B in the medium was almost the same.…”
Section: Discussionmentioning
confidence: 93%
“…These results suggested that B has an effect to increase the activity of ALP not only on bone marrow-derived cells but also on dental pulp-derived hDPSCs in the S-PRG filler-derived multi-ion system. Thus, the results above suggest the possibility that S-PRG fillers that slowly release B may contribute to promoting calcification in biological tissues, as well as the possibility that S-PRG fillers may promote mineralisation in dentin adjacent to the dental pulp, such as pulp-capping materials [33][34][35] . In addition, the comparison between E3 and the control medium showed the cell proliferation effect and ALP activity decreased in E3 compared with the control, despite that the concentration of B in the medium was almost the same.…”
Section: Discussionmentioning
confidence: 93%
“…Reinforcing the adhesive resin with fillers was expected to improve the mechanical properties and reduces the water sensitivity and solubility which increased the performance of the HL 3,4 . Consequently, many authors investigated the effect of addition of different fillers to dentin adhesives such as hydroxyapatite nanospheres, hydroxyapatite nanoparticles silica nanoparticles graphene oxide pre-reacted glassionomer filler [5][6][7]9,[22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…S-PRG filler can promote tertiary dentinogenesis. As pulp capping materials, several attempts have been made to incorporate S-PRG filler into adhesives [61,62], self-adhesive resins [63], and inorganic cements [64,65].…”
Section: Vital Pulp Therapymentioning
confidence: 99%